Understanding the influence of biota in the transfer of different sized microplastics between environmental compartments of marine ecosystem - Nagore Blasco; Mary Carolin Kurisingal; Philipp Hobmeier; Urtzi Izagirre; Manu Soto; Nerea García-Velasco (Environmental Chemistry and Ecotoxicology)
In addition to the microplastics (MPs) physical properties and the environmental hydrodynamic processes, the MP transport and distribution among the different marine environmental compartments is strongly influenced by the interaction with micro and macro biota. However, due to the methodological complexity and the lack of data there are nearly no models that consider the influence of biota on the transport of MPs. Thus, the aim of this study is to determine the influence of three ecologically relevant marine organism (Mytilus galloprovincialis, Hediste diversicolor, Palaemon elegans) from different compartments and feeding behaviour, in the transport and fate of two different size MPs (1 and 5 μm) between water column and sediment, through a microcosm experiment, during both exposure (5 days) and system depuration periods (14 days). Organisms were exposed to MPs through different experimental set ups: 1/5 treatment with 1 μm MPs spiked in seawater and 5 μm MP spiked in sediment, and 5/1 treatment with 5 μm and 1 μm MP spiked in seawater and sediment, respectively; both compartments were spiked with the same particle number. After experiment, organisms were subjected to procedures for both quantitative (alkaline digestion followed by filtration) and qualitative (cryosectioning) examination under fluorescence microscopy. All species accumulated MPs spiked in the water column and sediment irrespective of their habitat, and MPs appeared to transfer vertically by the influence of biota in relation to particle size. The three experimental organisms showed a higher accumulation of MPs spiked in the seawater column compared to sediment, with a trend of increased uptake for bigger particles. However, mussels were the only organisms able to depurate the accumulated MPs, with a significant reduction for smaller particles. Thus, mussels showed to be the main contributors to the vertical transport of MP present in the water column by ingestion and excretion processes, which might lead to the deposition of MPs through faeces in sediments, fostering their bioavailability for polychaetes and shrimps. MP of both sizes were found predominantly in the lumen of digestive tract of the three studied species, seemingly recording particle internalization in stomach epithelium of mussels.